Potency of Citrus reticulata Peel Extract as Active Compound of NonAlcohol Based Gel Hand Sanitizer - Santoso, Julyana Dika; Prasetyaningsih, Aniek; Madyaningrana, Kukuh (Universitas Kristen Duta Wacana, 2020)
Hand sanitizer is nowadays known as a part of one’s personal hygiene kit because of its practical use andeffectivity against skin microbes, such as Staphylococcus aureus. The common commercial hand sanitizers are madefrom alcohol which may have negative side effect like skin irritation. Utilization of active compounds from a plantthat has antibacterial compounds might be applied to the substitution of alcohol in the formulation of hand sanitizer.In this study, phytochemical compounds from Citrus reticulata and Citrus aurantifolia peel extracts were testedqualitatively and their antibacterial acitivity on Staphylococcus aureus were tested using disk diffusion method. Theresults showed that Citrus reticulata peel extract at the concentration of 70% was the most effective concentration ininhibiting Staphylococcus aureus. This certain concentration of Citrus reticulata peel extract was then chosen in the gelhand sanitizer formulation. Application of gel hand sanitizer with Citrus reticulata peel extract as its active compoundon the hands of respondents were also observed to inhibit bacterial growth. The use of peel extracts from Citrusspp, especially from Citrus reticulata might be potential in the formulation of non-alcohol based gel hand sanitizer.